O Vampiro de Niterói: uma leitura do caso à luz dos conceitos de perversão e fetichismo da psicanálise freudiana - Nogueira, Luísa Soares (2022)
This study aimed to read the case of serial killer Marcelo Costa de Andrade, "The Vampire of Niterói", based on the concepts of perversion and fetishism of the psychoanalytic approach, having as its main theoretical reference the Freudian strand. The hypothesis raised was that serial killers could be understood as perverse and fetishistic individuals, as far as their sexuality is concerned. Thus, their crimes would function as their main means of obtaining pleasure, based on pre-genital fantasies originating from an abnormality that occurred in the course of the development of their sexual constitution. At the end of the paper, a reflection was proposed about the challenges involved in listening to perverse patients from a psychoanalytic clinical perspective